Revitalisasi Taman Pendidikan Al-Qur’an (TPA) melalui Kolaborasi Relawan Mengajar di Desa Mekar Jaya - Ajeng Faridotul Ulfah; Mahmud Samsuri; Kurnia Dwi Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the revitalization of the Qur’anic Education Center (TPA) in Mekar Jaya Village, which had ceased operating due to the loss of its main teacher and limited volunteer support. Using a Participatory Action Research (PAR) approach, the program engaged community members, volunteers, religious leaders, and parents in collaborative efforts to restore regular Qur’an learning activities and strengthen the TPA’s function as a vital center of Islamic education. The intervention led to increased student participation, including the return of former learners and the enrollment of new participants, as well as improved learning motivation through active engagement and parental support. This collaborative revitalization not only revived essential Islamic learning for children but also fostered sustained community involvement, highlighting the critical role of volunteers and local leadership in sustaining nonformal religious education. The model developed through this initiative provides practical implications for other rural communities seeking to maintain and strengthen Islamic educational institutions.